Production ecology of bryophyte vegetation at Marion Island (Sub-Antarctic) - Russell, Shaun (Rhodes University, Faculty of Science, Botany Department, 1996)
The world's tundra regions can be considered as the last unexploited terrestrial biome on the earth's surface. Bryophytes contribute significantly to primary production and nutrient cycling in tundra habitats but received considerably less attention than the vascular plants during research for the Tundra Biome Project of the International Biological Programme in the 1970s. The IBP synthesis recognised this and called for more bryophyte production data and improved methodology in future studies. The synthesis also identitied the need for more information on within-site variability, energy/chlorophyll relationships and mineral nutrient studies where tundra bryophyte production patterns are concerned. Marion Island in the sub-Antarctic has an oceanic "tundra" type of vegetation, and the island offers the characteristics of an ideal "natural laboratory" for conducting fundamental ecological research particularly in the field of primary production and energy flow. Studies at Marion Island paralleled those of the IBP but also concentrated on the vascular component of the vegetation. Bryophytes contribute up to 60% of the biomass and 90% of plant cover in the mires that dominate the well-vegetated coastal plain of Marion Island. Following the termination of IBP research therefore it was decided to extend these studies during the 1980s by measuring growth and characterising the major factors influencing growth patterns in Marion Island bryophytes. In this thesis information is given on the physical and biotic environment of Marion Island. Data is presented on the cover, biomass, seasonal and annual production values, and turn-over rates (decomposition) of 15 bryophyte species found across the full range of habit at types at Marion Island. An analysis is also made of growth-associated variables viz. soils, climate, plant energy, chlorophyll. water and mineral nutrient contents. Production was found to be related broadly to moisture-related variables, overlain by nutrient factors in some instances. Higher absolute production figures were obtained than at other tundra sites and interesting phenological data are discussed. The results suggest that decomposition is controlled mainly by tissue degradability factors and that decomposition is more significant than production in controlling biomass accumulation. A model is given for production/decomposition patterns across the range of habitat conditions at Marion Island. Several growth measurement techniques were tested and recommendations are made concerning methodology for future bryophyte production studies. By reference to ecological data collected during the study.
Keywords: Bryophytes -- Marion Island (Prince Edward Islands) -- Ecology